Kontribusi Pajak Daerah dan Retribusi Daerah terhadap Pertumbuhan Ekonomi di Kabupaten Mandailing Natal (2021–2025) - Erni Yusnita Siregar (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study aims to analyze the magnitude of the contribution of Local Taxes and Local Retributions to economic growth in Mandailing Natal Regency over the last five-year period (2021–2025). Economic growth is measured by the Growth Rate of Gross Regional Domestic Product (GRDP). The research method uses secondary data obtained from the budget realization reports of the Regional Financial and Asset Management Agency (BPKAD) of Mandailing Natal, as well as GRDP data from the Central Statistics Agency (BPS) of Mandailing Natal Regency. The results indicate that although Local Taxes show an increasing trend, the contribution of Local Retributions still needs to be optimized to support infrastructure development that enhances local economic activities.